IMPROVING THE STRUCTURE OF ENGINEERING TRAINING WITHIN STRATEGIC PARTNERSHIP WITH COMPANIES - Vadim V. Karmanov; Svetlana V. Karmanova; Irina L. Gerasimchuk (Высшее образование в России)
The article considers the problem of training highly qualified specialists in conditions of economic modernization in the direction of creating highAtech industries. It is shown that one of the reasons for the insufficient level of professional training of engineers in this situation is transition to a system of academic education of bachelors and masters. Improving of the quality of engineering education can be ensured through the development and implementation of relevant programs of additional education in collaboration with industry. The article presents the experience of PNIPU specialists participation in the Presidential program for engineering personnel’s skills raising.